2021
DOI: 10.1080/08923973.2021.1931302
|View full text |Cite
|
Sign up to set email alerts
|

Promising drug repurposing approach targeted for cytokine storm implicated in SARS-CoV-2 complications

Abstract: A global threat has emerged in 2019 due to the rapid spread of Coronavirus disease (COVID-19). As of January 2021, the number of cases worldwide reached 103 million cases and 2.22 million deaths which were confirmed as the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). This global pandemic galvanized the scientific community to study the causative virus (SARS-CoV2) pathogenesis, transmission, and clinical symptoms. Remarkably, the most common complication associated with this disease is the cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 158 publications
0
3
0
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), made it necessary to repurpose existing drugs ( 1 ). Since an amplified inflammatory response leading to an uncontrolled cytokine release can be a consequence of SARS-CoV-2 infection, several anti-inflammatory drugs (glucocorticoids, non-steroidal anti-inflammatory drugs, interleukin antagonists, and kinase inhibitors) are being evaluated to be repositioned in COVID-19 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), made it necessary to repurpose existing drugs ( 1 ). Since an amplified inflammatory response leading to an uncontrolled cytokine release can be a consequence of SARS-CoV-2 infection, several anti-inflammatory drugs (glucocorticoids, non-steroidal anti-inflammatory drugs, interleukin antagonists, and kinase inhibitors) are being evaluated to be repositioned in COVID-19 ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The direct inhibition of the massive release of cytokines from hyperactivated immune cells serve as a therapeutic strategy for ALI and SARS-CoV-2 infection. 35 To date, traditional Chinese medicine, including QFPD, has been widely used for the treatment of patients with COVID-19. 36 Compared to modern medicines, herbbased TCMs have exhibited several merits, including pronounced curative effects, fewer side effects, and lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…Rivaroxaban shows a pleiotropic effect. Recent research data suggest that FXa possesses a function in the process of coagulation; additionally, it may have a proinflammatory effect [14]. It was assumed that the inhibition of FXa with rivaroxaban may induce antiinflammatory responses and protect the vascular endothelium from inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that treatment with rivaroxaban is associated with a reduction in a key inflammation and coagulation biomarkers, resulting in decreased levels of D-dimer, the thrombin-antithrombin III complex (TAT), high-sensitivity C-reactive protein (hs-CRP) and high-sensitivity interleukin-6 (hs-IL-6) [15]. Due to its anti-inflammatory effect, rivaroxaban may also have a potential pleiotropic role in patients infected with SARS-CoV-2 [14].…”
Section: Introductionmentioning
confidence: 99%